PERAN PENGARUH LOCUS OF CONTROL DAN PARENTAL INCOME TERHADAP PERILAKU MENABUNG PADA GEN Z YANG BEKERJA - Manurung, Harris (Universitas 17 Agustus 1945 Jakarta, 2024)
Financial attitude is an important matter for all young people, especially a student, in order to avoid all strange financial problems. Especially in this pandemic period it must be good at managing its finances appropriately so as not to experience waste. This study aims to explain financial literacy, lifestyle, locus of control, and parental income on student financial behavior in Central Java. The population in this study are students of Central Java province which numbered 400 respondents with the formula slovin. Purposive sampling technique by determining sample criteria. This research uses quantitative data obtained from questionnaire google form. Data were analyzed through multiple regression analysis with IBM SPSS Statistics 25. The results explain that financial literacy, lifestyle, locus of control, and parental income have a significant influence in student financial behavior in Central Java province.